The Influence of Leadership Style, Organizational Culture and Motivation on Teacher Performance at State Vocational School in the City of Depok the Academic Year 2022/2023 - Hadiyawati, Anis Syarifah; Sari, Agustin Rosiana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to examine and analyze the influence of leadership style, organizational culture, and motivation on teacher performance at SMK Negeri in Depok City. The variables in this study consisted of three independent variables, namely leadership style (X1), organizational culture (X2) and motivation (X3), and one variable, namely employee performance (Y). This research method is descriptive quantitative with a population of 268 teachers. Sampling was done by purposive sample generated by using the Slovin formula, the number of samples was 80 respondents consisting of teachers in all State Vocational Schools in Depok City. The data obtained from the distribution of research questionnaires. The analytical method used is multiple linear regression with the help of SPSS version 26 program. The results of this study indicate that partially the leadership style variable has no significant effect on teacher performance. However, organizational culture and motivation variables have a significant influence on teacher performance. Simultaneously, the three independent variables of leadership style, organizational culture and motivation have a significant effect on teacher performance at State Vocational Schools in Depok District for the 2022/2023 academic year.